Adjuvant chemotherapy, extent of resection, and immunoistochemical neuroendocrine markers as prognostic factors of early‐stage large‐cell neuroendocrine carcinoma - Claudio Andreetti; Mohsen Ibrahim; Antonio Gagliardi; Camilla Poggi; Giulio Maurizi; Domenico Armillotta; Valentina Peritone; Leonardo Teodonio; Erino Angelo Rendina; Federico Venuta; Marco Anile; Giovanni Natale; et al. (Thoracic Cancer, 2022)
Abstract Background We investigated whether adjuvant chemotherapy, extent of resection, and immunoistochemical neuroendocrine markers affected survival of patients with the early stage of large‐cell neuroendocrine cancer. Methods This was a retrospective multicenter study including consecutive patients undergoing resection of node negative large‐cell neuroendocrine carcinoma. Five‐year survival and disease‐free survival rate were evaluated by the Kaplan–Meier method and the log‐rank test in relation to adjuvant chemotherapy, extent of resection, and immunoistochemical neuroendocrine markers (synaptophysin, chromogranin A, and neuron‐specific enolase). Results Our study population included 117 patients; 47 (40%) of these received adjuvant chemotherapy. Patients treated with adjuvant chemotherapy had better survival (74% vs. 45%, p = 0.002) and disease‐free survival (79% vs. 40%, p = 0.001) in all cases except patients with tumor <20 mm (79.5% vs. 57.4%, p = 0.43). Lobectomy compared to sublobar resection was associated with better survival (67% vs. 0.1%, p < 0.0001) and disease‐free survival (65% vs. 0.1%, p < 0.0001) also in patients with tumor <20 mm (79% vs. 28%, p = 0.001). Patients with triple‐positive neuroendocrine markers had better survival (79% vs. 35%, p = 0.0001) and disease‐free survival (69% vs. 42%, p = 0.0008). Regression analysis showed that tumor size <20 mm, lobectomy, adjuvant chemotherapy, and triple‐positive immunistochemical neuroendocrine markers were significant favorable prognostic factors for survival outcomes. Conclusions Lobectomy seems to be the management of choice in patients with large‐cell neuroendocrine cancer <20 mm while adjuvant chemotherapy should be administered only in patients with tumor >20 mm.